Comparative transcriptome analyses of a table grape 'Summer Black' and its early-ripening mutant 'Tiangong Moyu' identify candidate genes potentially involved in berry development and ripening. Issue 1 (1st January 2020) - Wei, Lingzhu; Cao, Yuehua; Cheng, Jianhui; Xiang, Jiang; Shen, Biwei; Wu, Jiang
ABSTRACT: Early ripening is an important desirable attribute for fruit crops. 'Tiangong Moyu', a bud mutant of the grape cultivar 'Summer Black' ( Vitis vinifera L . × Vitis labrusca L . ), ripens nearly 10 days earlier and shows earlier increase in fresh weight, sugar accumulation, and color change and faster decrease in titratable acid than 'Summer Black'. To identify the genes controlling early fruit development and ripening in 'Tiangong Moyu', RNA-Seq profiles of the two cultivars were compared at five different berry developmental stages. Based on GO annotation and KEGG pathway enrichment analysis, the differentially expressed genes were clustered into various functional groups, including plant hormone signal transduction, transcription factors, anthocyanin-associated biosynthesis pathway, phenylpropanoid biosynthesis, plant–pathogen associated and plant–pathogen interaction, and ripening-related protein genes. Our results provided a global transcriptional profile of candidate genes involved in regulating berry development and ripening and a genetic basis for the understanding of grape berry ripening.